HOW NOT TO HATE ADVERTISING : a creative's guide to a long and (dare i say) happy career in a... remarkably silly industry. - Sonderup, Nick (ROUTLEDGE, 2026)
Written by an award-winning Chief Creative Officer (CCO) and featuring insights from agency and freelance advertising pros, this book is the creative professionals' guidebook, self-help book, and halftime speech/pep talk book all wrapped up in one. It's written for working creatives to help them sustain and succeed in an industry that has plenty to hate about it.This is not a "how to break into the business" book, and it doesn't aim to explain the creative process and how to come up with ideas. Instead, it accepts and expects that the reader has already done the hard part of breaking in and (hopefully) getting some work produced that they're proud of - it's the "what's next" to avoid burnout, filled with practical tips, sage advice, and real stories from an array of people who have definitely hated advertising at some point - but stuck with it anyway.A sort of treasure map that creatives can use to guide them through different stages of their career, this book is pure gold for advertising professionals and students who want to thrive in their chosen industry while taking care of their whole selves, now and into the future.
Keywords: Advertising -- Vocational guidance.; elektronické knihy; electronic books